IDNLearn.com is your reliable source for expert answers and community insights. Join our community to receive timely and reliable responses to your questions from knowledgeable professionals.

Express the formula [tex]P = 2l + 2w[/tex] in terms of the width, [tex]w[/tex]. Use the formula to find the width when the perimeter is 70 and the length is 22.

A. [tex]w = \frac{P - l}{2} ; w = 24[/tex]

B. [tex]w = \frac{P}{2} - l ; w = 13[/tex]

C. [tex]w = \frac{P - 2u}{2} ; w = 9[/tex]

D. [tex]w = P - 2l ; w = 26[/tex]


Sagot :

Certainly! Let's derive a formula for the width [tex]\( w \)[/tex] in terms of the perimeter [tex]\( P \)[/tex] and the length [tex]\( l \)[/tex] given the expression [tex]\( P = 2l + 2w \)[/tex].

1. Start with the perimeter formula:

[tex]\[ P = 2l + 2w \][/tex]

2. Isolate the terms involving width:

Subtract [tex]\( 2l \)[/tex] from both sides:

[tex]\[ P - 2l = 2w \][/tex]

3. Solve for width [tex]\( w \)[/tex]:

Divide both sides by 2:

[tex]\[ w = \frac{P - 2l}{2} \][/tex]

Now, using the perimeter [tex]\( P = 70 \)[/tex] and the length [tex]\( l = 22 \)[/tex], we can find the width using the derived formula.

[tex]\[ w = \frac{70 - 2 \cdot 22}{2} \][/tex]

Calculate the expression step-by-step:

1. Evaluate the multiplication inside the parentheses:

[tex]\[ 2 \cdot 22 = 44 \][/tex]

2. Subtract this value from the perimeter:

[tex]\[ 70 - 44 = 26 \][/tex]

3. Finally, divide by 2:

[tex]\[ \frac{26}{2} = 13 \][/tex]

Thus, the width [tex]\( w \)[/tex] is 13.

Let's cross-check this with the given options:

- [tex]\( w = \frac{P - l}{2} \)[/tex]

Substituting [tex]\( P = 70 \)[/tex] and [tex]\( l = 22 \)[/tex]:

[tex]\[ w = \frac{70 - 22}{2} = \frac{48}{2} = 24 \][/tex]

This is incorrect.

- [tex]\( w = \frac{P}{2} - l \)[/tex]

Substituting [tex]\( P = 70 \)[/tex] and [tex]\( l = 22 \)[/tex]:

[tex]\[ w = \frac{70}{2} - 22 = 35 - 22 = 13 \][/tex]

This is correct!

- [tex]\( w = \frac{P - 2l}{2} \)[/tex]

Substituting [tex]\( P = 70 \)[/tex] and [tex]\( l = 22 \)[/tex]:

[tex]\[ w = \frac{70 - 2 \cdot 22}{2} = \frac{70 - 44}{2} = \frac{26}{2} = 13 \][/tex]

This is also correct but not given in the same form as our derived formula.

- [tex]\( w = P - 2l \)[/tex]

Substituting [tex]\( P = 70 \)[/tex] and [tex]\( l = 22 \)[/tex]:

[tex]\[ w = 70 - 2 \cdot 22 = 70 - 44 = 26 \][/tex]

This is incorrect.

Based on the evaluation, the correct formula and corresponding value are:

[tex]\[ w = \frac{P}{2} - l \quad \Rightarrow \quad w = 13 \][/tex]
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Your questions deserve reliable answers. Thanks for visiting IDNLearn.com, and see you again soon for more helpful information.